THE VISION OF EQUALITY IN THE ACEH QANUN ON ADAT: AN APPROACH FROM THE LENS OF SHARI’A - Mustabsyirah M. Husein (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2018)
The philosophy of the Acehnese is Islam, the one which also becomes the cornerstone of landasan tradistional life. History has never raised any opposition to women in public activities. Custom- ary law as a cultural product is likely eroded by the times and the internal and external influ- ences as well. In the present context, the achievement of the past related to the role of women in the traditional sectors is still doubtful. The doubt is shown in the policy paradigm about cus- tomery law that apparently ignores the role of women and that seemingly restricts the roles of women in the development tasks. Some of the important indicators that concern are the legal basis used in the law, the use of certain words referred to women, women's participation in the formation of customary law and analysis of the substance in relation to the implementation. Custom is the foundation of nation building. The reconstruction efforts to rearrange the cultural life and customs that have been eroded for the order of the society and state are some of the things to do. Indeed the customary laws have opened up a partnership, but is still very limited and inconsistent, and is considered to be technical problems at the level of application. Reality is commonly used as a measure in measuring the application of a rule; when the social reality doesn’t show the existence of such partnership, this suggests the absence of the role of women as a development partner. Restoring the Acehnese living philosophy, i.e. Islamic teachings as a pillar of traditional life comprehensively at the level of policy application in the development of the nation is still absolutely necessary.